Dinamika Perjuangan Suku Kurdi Iraq dalam Memperoleh Status Wilayahnya di Iraq - Eriksa Gutama; Surwandono Surwandono; Ali Maksum (Universitas Muhammadiyah Sorong, 2022)
The purpose of this study is to explain the dynamics of the Iraqi Kurdish struggle before and after the saddam Hussein era. In this study, the authors explain how the dynamics of the Iraqi Kurdish struggle in obtaining regional autonomy as well as Saddam Hussein's political attitudes and leadership style. Iraq's still-fruitless Kurdish struggle with the crisis Baghdad is experiencing in the frame of a long conflict entering a phase of mutually hurting stalemate has led the two to choose the path of peace negotiations. Although Baghdad's peace treaty deal deal with the Kurds was hampered on the Kirkuk issue, with the phenomenon of the withdrawal of Iraqi troops from the UN protected zone and its migration of Saddam Hussein loyalists from the Territory of Northern Iraq made the opportunity for the Kurds to take over the region so that in 1992 under the shadow of the UN and allies, the KDP and PUK held free elections and established a Kurdistan Regional Government (KRG) for the Arbil region, Dohuk, and Sulaymanya. The KRG also turned the unarmed Peshmerga fighters into a regional defense force that would maintain peace and stability in the region. At this time the Kurds were able to create a safe and stable environment conducive to private and public investment.